Hadith #2741 - Sahih al-Bukhari - Humran bin Aban (Sahih al-Bukhari)
I was a companion rider of the Prophet (ï·º) on a donkey called âUfair. The Prophet (ï·º) asked, âO Mu`adh! Do you know what Allahâs right on His slaves is, and what the right of His slaves on Him is?â I replied, âAllah and His Apostle know better.â He said, âAllahâs right on His slaves is that they should worship Him (Alone) and should not worship any besides Him. And slaveâs right on Allah is that He should not punish him who worships none besides Him.â I said, âO Allahâ
Grade: Sahih

Hadith #3829 - Sahih al-Bukhari - Humran bin Aban (Sahih al-Bukhari)
The one who asked (the Prophet) was Gabriel (refer to Hadith 5.327).
Grade: Sahih

Hadith #6032 - Sahih al-Bukhari - Humran bin Aban (Sahih al-Bukhari)
While I was a companion rider with the Prophet (ï·º) he said, âO Mu`adh!â I replied, âLabbaik wa Sa`daik.â He repeated this call three times and then said, âDo you know what Allahâs Right on His slaves is?â I replied, âNo.â He said, Allahâs Right on His slaves is that they should worship Him (Alone) and should not join partners in worship with Him.â He said, âO Mu`adh!â I replied, âLabbaik wa Sa`daik.â He said, âDo you know what the right of (Allahâs) salves on
Grade: Sahih